2016
DOI: 10.3386/w22600
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Network Competition and Adverse Selection: Evidence from the Massachusetts Health Insurance Exchange

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 27 publications
3
74
0
Order By: Relevance
“…Pinkovskiy (2014) estimates that these laws essentially eroded all of the gains from managed care in the mid-1990s. There are related concerns that expanded use of limited network plans could increase selection in insurance markets, with insurers excluding the most expensive providers to avoid the sickest patients; Shepard (2015) argues that this was the case for growth of some limited network plans in Massachusetts.…”
Section: Discussionmentioning
confidence: 99%
“…Pinkovskiy (2014) estimates that these laws essentially eroded all of the gains from managed care in the mid-1990s. There are related concerns that expanded use of limited network plans could increase selection in insurance markets, with insurers excluding the most expensive providers to avoid the sickest patients; Shepard (2015) argues that this was the case for growth of some limited network plans in Massachusetts.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, we have little understanding of the quality of care provided in MA plan networks and plans’ selection of hospitals and physician providers. A Massachusetts study found that plans with narrow networks excluded hospitals with higher star ratings more frequently than did plans with broader networks 4 and often excluded other prestigious but expensive research institutions. 9 Qualitatively, both insurance companies and hospital executives have described controlling costs by limiting access to certain facilities as a key strategy, particularly with the introduction of the Affordable Care Act.…”
mentioning
confidence: 99%
“…In contrast to most of this literature, which has focused on average behavioral responses, our focus here is on the potential individual heterogeneity in the behavioral response and its implications (in this case, for risk scoring). In this sense, our paper relates to previous work analyzing the role of heterogeneity in the behavioral response in contributing to adverse selection in an employer-provided health insurance setting (Einav et al 2013a; Shepard 2015). …”
mentioning
confidence: 86%